2015
DOI: 10.1080/02786826.2015.1100710
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation and Calibration of Three Low-Cost Particle Sensors for Particulate Matter Measurement

Abstract: Particle sensors offer significant advantages of compact size and low cost, and have recently drawn great attention for usage as portable monitors measuring particulate matter mass concentrations. However, most sensor systems have not been thoroughly evaluated with standardized calibration protocols, and their data quality is not well documented. In this work, three low-cost particle sensors based on light scattering (Shinyei PPD42NS, Samyoung DSM501A, and Sharp GP2Y1010AU0F) were evaluated by calibration meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
290
6
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 371 publications
(327 citation statements)
references
References 31 publications
12
290
6
2
Order By: Relevance
“…One of the disadvantage is that the response of the low-cost particle sensors varies with particle composition and size distributions, which requires repeated calibration to ensure reliable estimations of mass concentration. This disadvantage has been reported by several groups (Wang et al, 2015;Sousan et al, 2016). However, there is no sufficient study of the reasons and quantification for such variations; nor approaches proposed to enhance the accuracy.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…One of the disadvantage is that the response of the low-cost particle sensors varies with particle composition and size distributions, which requires repeated calibration to ensure reliable estimations of mass concentration. This disadvantage has been reported by several groups (Wang et al, 2015;Sousan et al, 2016). However, there is no sufficient study of the reasons and quantification for such variations; nor approaches proposed to enhance the accuracy.…”
Section: Introductionmentioning
confidence: 79%
“…The signal from the Sharp GP2Y is dependent on the particle composition and size distribution. Our earlier work has demonstrated that for the same mass concentration of different particle types (e.g., NaCl, sucrose, and NH 4 NO 3 ) and size distributions (e.g., 300 nm, 600 nm, and 900 nm polystyrene latex particles), the sensor signal outputs were different (Wang et al, 2015). However, the patterns of the change, together with the necessity of calibration, has not been clearly presented.…”
Section: Experimental Set Upmentioning
confidence: 99%
See 3 more Smart Citations